Prevalence, antibiotic resistance patterns, and virulence factors of Staphylococcus aureus isolates associated with bovine mastitis in northern Bangladesh - Md. Mominul Islam; Md. Imran Hossain; Md. Sadequl Islam; Md. Golam Azam; Sajeda Sultana (Heliyon)
Staphylococcus (S.) aureus is a major cause of bovine mastitis and is notorious for its capacity to resist antibiotics, presenting substantial risks to both livestock and human health. The aim of this research was to assess the prevalence of S. aureus in bovine mastitis cases, as well as to examine their patterns of antimicrobial resistance and virulence genes contributing to mastitis in cattle. For this study, 120 milk samples were gathered from clinically mastitis affected cows across three districts in the northern part of Bangladesh. The detection and confirmation of S. aureus involved standard microbiological and biochemical techniques. The antibiotic sensitivity of the strains was evaluated using the disk diffusion method with a variety of antibiotics frequently used in veterinary settings. Furthermore, PCR was utilized to explore the presence of virulence genes linked to the pathogenicity of S. aureus. Findings revealed that out of the sampled cases, 56 strains of S. aureus were isolated, indicating a prevalence rate of 46.66 % in cases of clinical mastitis. The results revealed a diverse range of antibiotic resistance patterns among the isolates, with a notable prevalence of resistance to penicillin (100 %), ampicillin (85 %), amoxicillin (75 %), tetracycline (66 %), chlortetracycline (64 %), azithromycin (57 %), kanamycin (54 %), and gentamicin (50 %). 36 isolates out of 56 (64 %) were multidrug resistant in nature. Furthermore, virulence gene profiling identified the genes responsible for biofilm formation (bap), adhesion, inflammation and tissue damage (seb, pvl), and toxin production (hla and hlb), indicating the potential pathogenicity of the isolates. Notably, 12 isolates (21.42 %) harbored gene linked to methicillin resistance (mecA), raising concerns about the potential transmission of antimicrobial-resistant S. aureus strains from dairy cows to humans through the food chain. These findings underscore the critical importance of implementing stringent antimicrobial stewardship practices and surveillance measures in dairy farming to mitigate the dissemination of antibiotic resistance.